Application of Hybrid Artificial Algae Algorithm for Dynamic Economic Load Dispatch Problem - Kansal, Veenus; Dhillon, J.S. (2021 IEEE 2nd International Conference On Electrical Power and Energy Systems (ICEPES), 2021)
This paper presents hybrid artificial algae algorithm to solve dynamic economic load dispatch problem. The proposed hybrid artificial algae algorithm is the hybridization of artificial algae algorithm and simplex search method. The proposed artificial algae algorithm replicates the lifespan of microalgae which includes the helical movement phase, evolutionary phase, and adaptation phase. During the helical movement phase the exploration is preformed and evolutionary and adaptation phase gives the exploitation of search space. In the helical movement the provided exploration completely depends upon shear-force and energy parameters. In this algorithm, the artificial algae algorithm is a global optimizer while the simplex search method provides a local search. The simplex search/local search method enhances the exploitation capability by performing an iterative local search. The imposed equality constraints of the dynamic economic load dispatch problem has been handled by a proportionate power-sharing iterative search.